The effects of nationality differences and work stressors on work adjustment for foreign nurse aides - Yang Hsieh; Huang Fen (BMC, 2011)
Abstract Background The main purpose of this study was to discuss the nationality differences of foreign nurse aides and the effect of work stressors influencing work adjustment. And of helping them adapt to Taiwanese society, we summarized the difficulties that foreign nurse aides face in Taiwan. Methods The subjects included 80 foreign nurse aides from the Philippines, Indonesia, and Vietnam who worked in long-term care facilities in Tao Yuan County. We recruited volunteers at the participating facilities to complete the anonymous questionnaires. The return rate of the questionnaire was 88.75%. The validated instruments of Hershenson's (1981) and Schaefer and Moos (1993) were adopted to measure work stressors and work adjustment, respectively. A forward-backward translation process was used in this study. Results Indonesian foreign nurse aides respect their work, and are better workers than Vietnamese and Filipino nurse aids in many respects, which shows how the nationality of the foreign nurse aides might affect work adjustment. The stress created from patient care tasks influenced the foreign nurse aides' personal relationships at work and also affected their attitude when they performed their tasks. In addition, pressure from their supervisors might have affected their work skills, work habits, personal relationships, self-concepts or work attitudes. Moreover, a heavy workload and improper scheduling might have affected the personal relationships and work attitudes of the foreign nurse aides. It was found that work stressors had a significant correlation with work adjustment. Conclusions The results of the present study indicate that training programs are important factors for work adjustment among foreign nurse aides. Furthermore, celebration and leisure activities could be provided to release them from work stressors. More effort should be put into improving the working environment, namely providing a more supportive and enriching atmosphere. Based on these findings, we have a better understanding of how to assist foreign nurse aides in the future.